2018
DOI: 10.12965/jer.1836194.097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of circuit training on body composition, physical fitness, and metabolic syndrome risk factors in obese female college students

Abstract: The purpose of this study was to investigate the effect of a 12-week circuit training program on health-related physical fitness and metabolic syndrome risk factors in obese female college students. Twenty subjects with over 30% of accumulated body fat voluntarily participated and were randomly allocated to the control group (n=10) or circuit training group (n=10). The circuit training program consisted of 10 types of resistance and aerobic exercise and was performed 3 times per week for 12 weeks. Health-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 24 publications
6
23
0
2
Order By: Relevance
“…Another seminal study that has shaped the field is the one by Eriksson et al (1997) who reported conclusions comparable to those of Miller et al Their results support a strong and negative association ( r = –0.73; p < 0.05) between increased SM mass and HbA1c in middle-aged men and women diagnosed with T2D in response to 3 months of circuit-style RT ( Eriksson et al, 1997 ). Since, a growing body of evidence support circuit-style RT as an effective training modality to enhance metabolic health components, such as whole-body glucose homeostasis ( Kolahdouzi et al, 2019 ) body composition and physical fitness ( Kim et al, 2018 ) and pro-inflammatory cytokine profile ( Kolahdouzi et al, 2019 ). One clear advantage of such a training protocol is its similarity to aerobic exercise from the perspective of the broad continuum of the energy systems, according to its ability to induce an elevated cardiovascular response ( Gotshalk et al, 2004 ).…”
Section: Narrative Literature Reviewmentioning
confidence: 99%
“…Another seminal study that has shaped the field is the one by Eriksson et al (1997) who reported conclusions comparable to those of Miller et al Their results support a strong and negative association ( r = –0.73; p < 0.05) between increased SM mass and HbA1c in middle-aged men and women diagnosed with T2D in response to 3 months of circuit-style RT ( Eriksson et al, 1997 ). Since, a growing body of evidence support circuit-style RT as an effective training modality to enhance metabolic health components, such as whole-body glucose homeostasis ( Kolahdouzi et al, 2019 ) body composition and physical fitness ( Kim et al, 2018 ) and pro-inflammatory cytokine profile ( Kolahdouzi et al, 2019 ). One clear advantage of such a training protocol is its similarity to aerobic exercise from the perspective of the broad continuum of the energy systems, according to its ability to induce an elevated cardiovascular response ( Gotshalk et al, 2004 ).…”
Section: Narrative Literature Reviewmentioning
confidence: 99%
“…We confirm that Circuit Weight training can significantly increase flexibility. A study conducted in Korea on flexibility shows that the Circuit is the main capital to increase flexibility in obese Female, it is because in the Circuit implements high training intensity and frequency of aerobic exercise drills (Kim et al, 2018). Kang and Lee (2012) also reported the same results that the effects of circuit weight training for 12 weeks effectively increased flexibility.…”
Section: The Effects Of Circuit Weight Training For Physical Fitnessmentioning
confidence: 87%
“…All values were expressed as mean±standard deviation. P<0.05 was considered significant (Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations